Comparative effect of water extract of parthenium hysterophorus, Datura alba, Phragmites australis and Oryza sativa on weeds and wheat - Riaz Ahmad Afridi,; Muhammad Azim Khan, (Universiti Kebangsaan Malaysia, 2015)
Laboratory and pot experiments were conducted at the Department of Weed Science, The University of Agriculture Peshawar, Pakistan during fall 2011 and repeated in 2012. Allelopathic plants were used against wheat and associated weeds. Allelopathic plants showed significant activity against three selected species - Triticum aestivum, Avena fatua and Rumex crispus. Aqueous extracts of Parthenium hysterophorus and Datura alba showed significant effect against weeds of Triticum aestivum although aqueous extract of Phragmites australis possessed moderate activity. It was noted that aqueous extract of Oryza sativa and control were comparable for all parameters studied. Aqueous extract of P. hysterophorus and D. alba decreased seed germination, shoot length, fresh and dry biomass as compared to the rest of the treatments. The degree of toxicity of different treatments can be placed in the following order of inhibition: P. hysterophorus > D. alba > P. australis > O. sativa ≥ control. The present studies showed that the plants used contain water soluble allelochemicals that retard or inhibit the germination, growth and biomass of other species. These experiments suggests that P. hysterophorus, D. alba and P. australis extracts may have negative effect on major weeds like A. fatua and R. crispus. Thus there is a possibility of using these plant extracts for weed management. However, more extensive studies is required to identify the allelopathins responsible for inhibitory effects on seed germination and plant growth.